Ouverture de ‘Special Issue on Start-Up Ecosystem’ - Silvio M. Brondoni (Symphonya, 2016)
Symphonya. Emerging Issues in Management launches a new editorial line called 'Special Issue on' aimed at promoting Symphonya's specific vocation to maintaining a close link between the academic world and the business world through in-depth analyses of 'emerging issues' that managers are facing in global markets. This Special Issue is dedicated to the theme of the creation of new businesses. In today's competitive environment characterised by globalised markets, oversupply and a trend towards concentration in most sectors, innovation is a requisite factor for the survival of enterprises and the territories in which they operate. The Italian Start-up Act, introduced in late 2012 and incrementally enriched in subsequent years, is indeed a remarkable policy in a comparative context. Italian start-ups have been endowed with real, diverse and potentially high-impact instruments to find their own way to market and to success.